Religiousness and Family Support among Female Activists in Islamic Organizations: Phenomenological Study - Husnul Khotimah; Sri Lestari (Jurnal Psikologi Islam dan Budaya, 2024)
This research aims to understand the balance between family and organization among women activists of the Islamic Community Organization (Ormas) of the Special Region of Yogyakarta. This research uses a qualitative approach with an Interpretative Phenomenological Analysis (IPA) design. Eight women who had been active in the organization for at least five years were the participants. Data were collected using semi-structured interviews and recorded with audio recording. The research results show that female mass organization activists feel capable of helping, amar ma'ruf nahi munkar, serving the people, and being valuable people. Participants received family support from husbands and parents. Husbands support participants in being committed to the organization and willing to share roles in household matters and childcare. Meanwhile, support from parents takes the form of encouragement to continue being active in the organization and helping to look after children when participants are active. For women with dual roles in the family and organization, social support is essential to balance roles in the family and organization.